Method and material for enhancing the coercivity of two-dimensional iron germanium telluride nanosheets by oxidizing induction of amorphous pinning regions

CN122957797APending Publication Date: 2026-10-23NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611459584.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本发明旨在解决现有二维铁锗碲磁性能调控方案成本较高、处理规模有限,提供了一种提高二维铁锗碲纳米片矫顽力的方法

Benefits of technology

[0020]第一,本发明利用空气或其他含氧气氛作为后处理介质,不需要构筑复杂异质结、逐片制备电极或持续施加外场,设备需求低、操作简单。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957797A_ABST
    Figure CN122957797A_ABST
Patent Text Reader

Abstract

The application discloses a method for enhancing the coercivity of two-dimensional iron germanium tellurium nanosheets by oxidizing and inducing amorphous pinning regions, and belongs to the technical field of preparation and magnetic performance regulation of two-dimensional magnetic materials. Blocky iron germanium tellurium material is subjected to cathode electrochemical intercalation stripping, centrifugal cleaning and solid-liquid separation, so that the surface of the nanosheet is fully exposed; then the obtained nanosheet powder is placed in an oxygen-containing atmosphere for controlled oxidation; while the crystalline matrix is retained, a spatially discrete nanoscale amorphous region is formed on the surface. Characterization shows that the crystalline structure and the amorphous structure coexist after oxidation, X-ray photoelectron spectroscopy shows that the oxygen signal is enhanced and a Fe 3+ related oxidation peak appears. The amorphous region locally pins the magnetic domain wall movement, so that the coercivity of the sample after treatment is higher than that of the unoxidized sample under the same measurement conditions. The application has the advantages of simple process, low cost and suitability for post-regulation of the magnetic performance of batch two-dimensional iron germanium tellurium nanosheets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of two-dimensional magnetic material preparation and magnetic property control technology, specifically to a method for controlling the oxidation of two-dimensional iron-germanium-tellurium nanosheets obtained by electrochemical intercalation and exfoliation, thereby forming discrete oxidation-induced amorphous regions while retaining the crystalline iron-germanium-tellurium matrix, thus enhancing the coercivity of the material, and the two-dimensional iron-germanium-tellurium magnetic material obtained by this method. Background Technology

[0002] Two-dimensional materials typically have lateral dimensions much larger than their thickness. Their degrees of freedom, such as electrons, phonons, and spins, are confined in a low-dimensional environment, allowing them to exhibit electrical, optical, thermal, and magnetic properties distinct from their bulk counterparts. Magnetocrystalline anisotropy allows some layered materials to retain long-range magnetic order even after being thinned to a two-dimensional scale, making two-dimensional ferromagnetic materials candidate materials for high-density magnetic storage, spintronic devices, and magnetic sensors.

[0003] Iron-germanium-tellurium material Fe 3-x GeTe2 (FGT) is a class of two-dimensional ferromagnetic materials with a layered van der Waals structure and out-of-plane magnetic anisotropy. Its coercivity reflects the external magnetic field strength required to overcome the energy barrier when the magnetization direction reverses, and is an important indicator for evaluating magnetization stability. Existing control methods include changing the stoichiometry, constructing heterojunctions, electrostatic doping, current-driven magnetization, strain modulation, laser processing, and molecular adsorption. However, a significant portion of these methods rely on sheet-by-sheet transfer, fine micro / nano fabrication, or continuous external drive, which is not conducive to low-cost post-processing of batches of nanosheets. Summary of the Invention

[0004] This invention aims to address the limitations of existing two-dimensional iron-germanium-tellurium magnetic property modulation schemes, which suffer from high costs and limited processing scale, and provides a method for improving the coercivity of two-dimensional iron-germanium-tellurium nanosheets.

[0005] To address the aforementioned technical problems, this invention provides a method for improving the coercivity of two-dimensional iron-germanium-tellurium nanosheets, comprising the following steps:

[0006] S1, using bulk iron-germanium-tellurium material as a cathode for electrochemical cation intercalation, thereby increasing the interlayer spacing of the bulk iron-germanium-tellurium material;

[0007] S2, the intercalated iron-germanium-tellurium material is placed in an organic solvent and mechanically disturbed to obtain a dispersion containing two-dimensional iron-germanium-tellurium nanosheets;

[0008] S3, the dispersion is centrifuged and washed multiple times, the upper suspension containing two-dimensional nanosheets is collected, and then filtered and vacuum dried in sequence to obtain two-dimensional iron-germanium-tellurium nanosheets.

[0009] S4, the two-dimensional iron-germanium-tellurium nanosheets are placed in an oxygen-containing atmosphere for controlled oxidation treatment, so that while retaining the crystalline iron-germanium-tellurium matrix, the two-dimensional iron-germanium-tellurium nanosheets form spatially separated oxidation-induced amorphous regions on the surface of the crystalline iron-germanium-tellurium matrix.

[0010] Furthermore, the stoichiometric formula for the bulk iron-germanium-tellurium material is Fe. 3-x GeTe2, where 0≤x≤0.15, has a hexagonal crystal system with space group P63 / mmc.

[0011] Furthermore, the electrochemical cation intercalation employs a dual-electrode system, where a bulk iron-germanium-tellurium material is fixed on a platinum sheet, platinum wire, or platinum rod as a cathode, and another platinum electrode serves as an anode. The cathode and anode are immersed in an electrolyte containing quaternary ammonium salts and aprotic organic solvents. The cathode is at a negative potential relative to the anode, thereby driving the larger quaternary ammonium cations into the van der Waals interlayer, weakening the coupling between adjacent iron-germanium-tellurium layers. The intercalated bulk material expands due to the increased interlayer spacing.

[0012] Furthermore, the aprotic organic solvent is propylene carbonate or N,N-dimethylformamide; the quaternary ammonium salt is selected from any one of tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium bromide and tetraheptylammonium bromide.

[0013] Furthermore, the concentration of quaternary ammonium salt in the electrolyte is 0.5M; the distance between the cathode and anode is 1~1.5cm; the potential difference between the cathode and anode is 15~35V; the cathode potential is a negative DC potential; and the electrolysis time is 20min.

[0014] Furthermore, the intercalated iron-germanium-tellurium material is placed in an organic solvent, propylene carbonate or N,N-dimethylformamide, and mechanical disturbance is applied by ultrasound, oscillation or a combination thereof to cause the nanosheets to peel off from the bulk material and form a suspension.

[0015] Furthermore, the mechanical disturbance is treated with ultrasound, with an ultrasonic power of 100W and a processing time of 30–90 seconds.

[0016] Furthermore, the dispersion is subjected to multiple centrifugal washing processes. Specifically, the dispersion is centrifuged at high speed (12000~16000 r / min), the supernatant is removed, a washing medium is added and the precipitate is redispersed, and this process is repeated multiple times to remove residual electrolytes, intercalating agents and byproducts. Subsequently, the unexfoliated thick blocks are removed by centrifugation at low speed (1000~1500 r / min), and the upper suspension containing two-dimensional nanosheets is collected. The washing medium can be propylene carbonate, N,N-dimethylformamide or anhydrous ethanol.

[0017] Furthermore, the upper suspension containing two-dimensional nanosheets is filtered and vacuum dried to obtain two-dimensional iron-germanium-tellurium nanosheet powder.

[0018] Furthermore, the two-dimensional iron-germanium-tellurium nanosheets are placed in an oxygen-containing atmosphere for controlled oxidation treatment, so that while retaining the crystalline iron-germanium-tellurium matrix, the two-dimensional iron-germanium-tellurium nanosheets form spatially separated oxidation-induced amorphous regions on the surface of the crystalline iron-germanium-tellurium matrix. The controlled oxidation can be carried out by natural oxidation, i.e., placing it in air for 5 hours to 5 days; or by heating oxidation, i.e., treating it in air at 80 to 150°C for 15 to 60 minutes.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] First, the present invention uses air or other oxygen-containing atmospheres as the post-processing medium, which eliminates the need to construct complex heterojunctions, fabricate electrodes one by one, or continuously apply external fields, resulting in low equipment requirements and simple operation.

[0021] Second, electrochemical intercalation stripping, centrifugal washing, and solid-liquid separation can yield powders composed of a large number of nanosheets, enabling oxidation regulation to be carried out in batches, rather than being limited to individual mechanically stripped sheets.

[0022] Third, this invention does not aim for a continuous and dense surface oxide layer, but rather controls the formation of discrete amorphous regions dispersed on the surface of a crystalline substrate. This composite microstructure provides local structural discontinuity while retaining the main ferromagnetic phase, which is beneficial for hindering the movement of magnetic domain walls and increasing the external field required for magnetization reversal.

[0023] Fourth, existing research generally considers Fe 3-x The air oxidation of GeTe2 causes magnetic signal attenuation. However, this invention observed an increase in coercivity from approximately 3300 Oe to approximately 4300 Oe in specific nanosheet powders and processing windows, demonstrating a technical effect distinct from the general expectation of oxidation degradation. Compared to morphological comparison alone, selected area electron diffraction, local fast Fourier transform of high-resolution images, and X-ray photoelectron spectroscopy together constitute a multi-scale evidence chain for the preservation of the bulk crystalline state, local amorphization, and changes in surface oxidation valence states.

[0024] Fifth, the natural oxidation time, heating temperature, and heating time can all be used as process parameters, providing an adjustable means to establish the correspondence between the size, number density, and coercivity of amorphous regions. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the overall process of the method of the present invention.

[0026] Figure 2The image shows a transmission electron microscope image of the two-dimensional iron-germanium-tellurium nanosheets that were dispersed in anhydrous ethanol, centrifuged, washed, vacuum filtered and dried in Example 1, without controlled oxidation. The scale bar is 50 nm.

[0027] Figure 3 The image shows a transmission electron microscope image of two-dimensional iron-germanium-tellurium nanosheets after natural oxidation in air for 5 hours in Example 1. The circles indicate representative nanoscale amorphous regions, and the scale bar is 50 nm.

[0028] Figure 4 The selected area electron diffraction pattern of the uncontrolled oxidized two-dimensional iron-germanium-tellurium nanosheets in Example 1 is shown, with a scale bar of 5 nm. -1 .

[0029] Figure 5 This is the selected area electron diffraction pattern of the two-dimensional iron-germanium-tellurium nanosheets after natural oxidation in air for 5 hours in Example 1. The scale bar is 5 nm. -1 .

[0030] Figure 6 The images shown are high-resolution transmission electron microscope images and local fast Fourier transform images of two-dimensional iron-germanium-tellurium nanosheets after natural oxidation in air for 5 hours in Example 1. (a) is a high-resolution image, with the red and blue boxes indicating the amorphous and crystalline regions, respectively, and the scale bar is 5 nm; (b) is the fast Fourier transform image of the red box region; and (c) is the fast Fourier transform image of the blue box region.

[0031] Figure 7 The X-ray photoelectron spectra of two-dimensional iron-germanium-tellurium nanosheet powders after uncontrolled oxidation in Example 1 and natural oxidation in air for 5 days in Example 4 are shown. (a) and (b) are the full spectrum and Fe2p fine spectrum of the uncontrolled oxidation sample, respectively, and (c) and (d) are the full spectrum and Fe2p fine spectrum of the sample after natural oxidation for 5 days, respectively.

[0032] Figure 8 The hysteresis loop of the uncontrolled oxidized two-dimensional iron-germanium-tellurium nanosheets in Example 1 at 2K.

[0033] Figure 9 The hysteresis loop of the two-dimensional iron-germanium-tellurium nanosheets after natural oxidation in air for 5 days in Example 4 is shown at 2K.

[0034] Figure 10 The image shows a transmission electron microscope image of two-dimensional iron-germanium-tellurium nanosheets obtained by heating in air at 100°C for 15 min and then stopping the heating and cooling in Example 2. The circles indicate representative nanoscale amorphous regions, and the scale bar is 50 nm.

[0035] Figure 11The image shows a transmission electron microscope image of two-dimensional iron-germanium-tellurium nanosheets obtained by natural oxidation in air for 10 hours in Example 3. The circles indicate representative nanoscale amorphous regions, and the scale bar is 50 nm.

[0036] Figure 12 The image shows a transmission electron microscope image of two-dimensional iron-germanium-tellurium nanosheets obtained by natural oxidation in air for 5 days in Example 4. The circles indicate representative nanoscale amorphous regions, and the scale bar is 50 nm.

[0037] Figure 13 The diagram illustrates the mechanism of magnetic domain wall motion in unoxidized nanosheets and nanosheets with discrete amorphous regions after controlled oxidation. In the diagram, (a) represents an unoxidized nanosheet and (b) represents a nanosheet after controlled oxidation. Detailed Implementation

[0038] The present invention will be further described below with reference to the accompanying drawings and embodiments. The embodiments are provided to enable those skilled in the art to understand and implement the invention, and are not intended to limit the scope of protection to the specific values, equipment models, or operating sequences listed. Where there is no contradiction, the technical features of the various embodiments can be combined with each other.

[0039] Existing literature reports that natural oxidation forms a continuous oxide layer, which often leads to a deterioration in saturation magnetization. In this field, iron-germanium-tellurium oxidation is generally regarded as a negative phenomenon that needs to be avoided (h-BN packaging is commonly used in device fabrication to isolate air and prevent oxidation). However, this application takes the opposite approach, actively controlling oxidation and deliberately creating discrete pinning sites to transform harmful oxidation into a favorable microstructure, which is not a conventional technical approach for those skilled in the art.

[0040] This invention provides a cathode electrochemical cation intercalation Fe 3-x A complete technical solution is implemented, consisting of GeTe2 nanosheets, mechanically exfoliated intercalated materials, centrifugal cleaning and solid-liquid separation to obtain bare surface samples, controlled oxygen-containing atmosphere oxidation to generate discrete amorphous oxide islands, and magnetic domain wall pinning to enhance coercivity. This involves first preparing a large number of two-dimensional nanosheets with a bare surface through electrochemical cation intercalation, mechanically disturbed liquid-phase exfoliation, and centrifugal cleaning, ensuring the surface is accessible to the atmosphere. Then, controlled oxidation is used to deliberately generate spatially discrete, unconnected amorphous oxide islands. A large area of ​​the matrix retains crystalline ferromagnetic ferromagnetic domains (FGTs). Discrete pinning sites are designed to directionally enhance coercivity. Controlled oxidation does not oxidize or amorphize the entire material, but rather forms multiple spatially separated nanoscale amorphous regions on the nanosheet surface while preserving the crystalline iron-germanium-tellurium matrix. The processing intensity is controlled based on the principle of generating observable spatially discrete amorphous regions on the nanosheet surface while preserving the main crystalline structure. If oxidation causes the nanosheets to lose their crystalline structure or magnetism, it is not considered a preferred controlled oxidation window.

[0041] The specific steps of the method described in this invention are as follows:

[0042] S1, using bulk iron-germanium-tellurium material as a cathode for electrochemical cation intercalation, thereby increasing the interlayer spacing of the bulk iron-germanium-tellurium material;

[0043] S2, the intercalated iron-germanium-tellurium material is placed in an organic solvent and mechanically disturbed to obtain a dispersion containing two-dimensional iron-germanium-tellurium nanosheets;

[0044] S3, the dispersion is centrifuged and washed, the upper suspension containing two-dimensional nanosheets is collected, and then filtered and vacuum dried in sequence to obtain a solid sample composed of a large number of two-dimensional iron-germanium-tellurium nanosheets, and the surface of the nanosheets can be in contact with the atmosphere.

[0045] S4, the solid sample is placed in an oxygen-containing atmosphere for controlled oxidation treatment, so that the two-dimensional iron-germanium-tellurium nanosheets retain the crystalline iron-germanium-tellurium matrix while forming spatially separated oxidation-induced amorphous regions on the surface of the crystalline iron-germanium-tellurium matrix.

[0046] The term "oxidation-induced amorphous region" as used in this specification refers to a nanoscale amorphous region that appears on the surface of a nanosheet after treatment in an oxygen-containing atmosphere and lacks long-range ordered lattice fringes relative to the surrounding crystalline matrix under a high-resolution transmission electron microscope. The fast Fourier transform frequency domain image of this region does not show the same regular spots as the adjacent crystalline matrix, while the frequency domain image of the adjacent crystalline matrix still shows ordered spots. This application uses "oxidation-induced" to indicate that it is formed after oxygen-containing treatment, but does not limit it to a single stoichiometric oxide.

[0047] Selected area electron diffraction (SED) was used to verify the preservation of the main crystalline structure over a larger selected area. Uncontrolled oxidation of nanosheets resulted in regular, discrete diffraction spots; nanosheets subjected to natural oxidation for 5 hours retained discrete diffraction spots while exhibiting diffuse diffraction rings. This combination indicates the coexistence of the processed crystalline structure and the absence of long-range ordered structures, corroborating the results of the high-resolution images and their local fast Fourier transform spatial resolution.

[0048] X-ray photoelectron spectroscopy was used to verify the surface chemical changes induced by oxygen-containing treatment. Powder subjected to natural oxidation for 5 days exhibited a stronger O1s signal compared to powder without controlled oxidation, and Fe2p fine spectra showed the presence of Fe2p. 3+ The relevant oxidation peaks indicate that the observed structural changes are accompanied by changes in the oxidation valence state of iron, rather than being caused solely by surface physisorption. Scanning transmission electron microscopy (STEM) energy loss spectroscopy (EDS) or electron energy loss spectroscopy can be used to further confirm the local elemental distribution in the amorphous region, but are not necessary conditions for implementing this invention.

[0049] The term "increased coercivity" in this specification refers to a greater absolute value of coercivity in the treated sample compared to a reference sample that has not undergone controlled oxidation, when both samples are subjected to hysteresis loop testing under the same measurement temperature, magnetic field direction, maximum magnetic field, and sweep procedure. It is preferable to obtain the treated and reference samples from the same preparation batch to minimize the impact of differences in thickness distribution, stoichiometry, and sample quality.

[0050] This invention also provides a coercivity-enhanced two-dimensional iron-germanium-tellurium magnetic material, which is a nanosheet powder. Each nanosheet has a crystalline iron-germanium-tellurium matrix and multiple spatially discrete oxidation-induced amorphous regions distributed on its surface. The material can be identified using one or more of high-resolution transmission electron microscopy, local fast Fourier transform, selected area electron diffraction, and X-ray photoelectron spectroscopy, allowing for identification based on the resulting composite microstructure and surface oxidation characteristics even when the specific exfoliation equipment or operating sequence is changed.

[0051] Example 1: Natural oxidation in air for 5 hours

[0052] (1) Take 5 pieces of Fe with a transverse dimension of about 3 mm. 3-x GeTe2 crystals were fixed with fine copper foil on a platinum sheet measuring 1 cm long, 1 cm wide, and 0.1 mm thick, serving as the cathode. Another platinum sheet of the same size was used as the anode, with the side of the fixed crystal facing the anode. The distance between the cathode and anode was approximately 1 cm. 5.56 g of tetrabutylammonium chloride was dissolved in 40 mL of propylene carbonate, and the cathode and anode were immersed in the resulting electrolyte. A DC potential of 0 V was applied to the anode, and a DC potential of -15 V was applied to the cathode for 20 minutes, causing the bulk crystal to undergo intercalation expansion.

[0053] (2) The expanded crystals were transferred to 20 mL of propylene carbonate, treated with 100 W ultrasonic power for 60 s and gently shaken to obtain a black suspension containing two-dimensional iron germanium tellurium nanosheets.

[0054] (3) Centrifuge the suspension at 12000 r / min for 45 min, remove the supernatant and add anhydrous ethanol to wash the precipitate to redisperse it. This process is repeated three times. After the third redisperse, centrifuge at 1500 r / min and collect the upper suspension to reduce the amount of thick clumps that have not been fully separated.

[0055] (4) The upper suspension was vacuum filtered through a 10 μm PTFE filter membrane. The sample on the filter membrane was scraped off and vacuum dried at room temperature to obtain unoxidized two-dimensional iron-germanium-tellurium nanosheet powder. The transmission electron microscope image is shown below. Figure 2 As shown, the selected area electron diffraction pattern is as follows: Figure 4 As shown, the X-ray photoelectron spectrum is as follows: Figure 7 As shown in (a) and (b) above, its hysteresis loop at 2K is as follows Figure 8As shown.

[0056] (5) The powder thin layer was spread and exposed to air for 5 hours to obtain a controlled oxidation sample with discrete nanoscale amorphous regions on the surface. Its transmission electron microscope morphology is shown in the figure. Figure 3 As shown, the selected area electron diffraction pattern is as follows: Figure 5 As shown, the high-resolution transmission electron microscope image and local fast Fourier transform diagram are as follows: Figure 6 As shown.

[0057] Example 2: Oxidation by heating in air for 15 min

[0058] Steps (1)-(4) are the same as in Example 1, except that:

[0059] In step (5), the powder is placed on a heating stage and heated in air at 100°C for 15 minutes. Heating is then stopped and the sample is cooled to obtain a controlled oxidation sample with discrete nanoscale amorphous regions on the surface. Its transmission electron microscope morphology is shown in the figure below. Figure 10 As shown.

[0060] Example 3: Natural oxidation in air for 10 hours

[0061] Steps (1)-(4) are the same as in Example 1, except that in step (5), a thin layer of powder is spread and exposed to air for 5 hours to obtain a controlled oxidation sample with discrete nanoscale amorphous regions on the surface. The morphology of the sample is shown in the transmission electron microscope image. Figure 11 As shown.

[0062] Example 4: Natural oxidation in air for 5 days

[0063] Steps (1)-(4) are the same as in Example 1, except that in step (5), a thin layer of powder is spread and exposed to air for 5 days to obtain a controlled oxidation sample with discrete nanoscale amorphous regions on the surface. The morphology of the sample is shown in the transmission electron microscope image. Figure 12 As shown, the X-ray photoelectron spectrum is as follows: Figure 7 As shown in (c) and (d) in the figure, its hysteresis loop at 2K is as follows Figure 9 As shown.

[0064] Characterization and performance testing:

[0065] (1) Transmission electron microscopy and selected area electron diffraction

[0066] Transmission electron microscopy (TEM) and selected area electron diffraction (SED) analyses were performed on both the uncontrolled oxidation two-dimensional iron-germanium-tellurium nanosheets and the controlled oxidation samples from Example 1. TEM analyses were also performed on the controlled oxidation samples from Examples 1-4. The specific analyses are as follows:

[0067] Two-dimensional iron-germanium-tellurium nanosheets (Example 1) that underwent electrochemical intercalation exfoliation, anhydrous ethanol dispersion and centrifugal washing, vacuum filtration and drying, and were not subsequently subjected to controlled oxidation, were observed using transmission electron microscopy. Figure 2 As shown, the nanosheets exhibit a continuous structure within the observed field of view, and no [other structures] were observed. Figure 3 The middle circle indicates several discrete amorphous regions.

[0068] Selected area electron diffraction was performed on the uncontrolled oxidized two-dimensional iron-germanium-tellurium nanosheets (Example 1). Figure 4 As shown, the diffraction pattern shows regularly arranged discrete spots, and no other observations were observed. Figure 5 The significant diffuse ring diffraction signal indicates that the sample before treatment has good crystalline order in the selected area. Figure 4 Used as a structural reference for subsequent oxidized samples.

[0069] A controlled oxidation sample (Example 1) obtained by exposing two-dimensional iron-germanium-tellurium nanosheet powder to air for 5 hours was observed using transmission electron microscopy. Figure 3 As shown, multiple spatially separated, shallowly contrasted nanoscale regions appear on the surface of the nanosheets. Figure 6 The high-resolution transmission electron microscope image (a) shows that it is an amorphous region lacking long-range ordered lattice fringes relative to the surrounding crystalline matrix. The main body of the nanosheet still retains the crystalline structure, indicating that the oxygen-containing treatment changed the local microstructure but did not make the nanosheet amorphous as a whole.

[0070] Selected area electron diffraction was performed on two-dimensional iron-germanium-tellurium nanosheets (Example 1) that had been naturally oxidized in air for 5 hours. Figure 5 As shown, the diffraction pattern retains discrete diffraction spots corresponding to the crystalline iron-germanium-tellurium matrix, while a distinct diffuse ring diffraction signal appears near the central spot. The coexistence of discrete spots and diffuse rings indicates that the selected region simultaneously contains both long-range ordered crystalline structures and structural components lacking long-range order, confirming on a larger selected scale that controlled oxidation does not lead to overall amorphization of the nanosheets.

[0071] The nanosheets (Example 1) after natural oxidation in air for 5 hours were further observed using high-resolution transmission electron microscopy and localized fast Fourier transform analysis. Figure 6 As shown in (a) above, the lighter contrast region indicated by the red box lacks continuous, regular lattice fringes, while the adjacent region indicated by the blue box still has relatively ordered lattice fringes. Figure 6 As shown in (b), the Fast Fourier Transform plot of the area within the red box does not exhibit regular hexagonal discrete spots; as... Figure 6 As shown in (c), the Fast Fourier Transform (FFT) plot of the blue-boxed region preserves discrete spots. This spatially resolved evidence indicates the existence of amorphous regions and a crystalline matrix within the same nanosheet field of view, and... Figure 5The selected area electron diffraction results corroborate each other.

[0072] Samples oxidized by heating in air for 15 min (Example 2), naturally oxidized in air for 10 h (Example 3), and naturally oxidized in air for 5 days (Example 4) were observed by transmission electron microscopy. The results are as follows: Figures 10-12 As shown, the surface of the sample oxidized in air for 15 min exhibits discrete, shallow-contrast amorphous regions, similar to the surface of the sample oxidized naturally in air for 5 h. The area of ​​a single amorphous region is similar to that of the sample oxidized naturally in air for 5 h, but the density of amorphous regions in the sample oxidized in air for 15 min is higher than that in the sample oxidized naturally in air for 5 h. The surface of the sample oxidized naturally in air for 10 h exhibits discrete, shallow-contrast amorphous regions, similar to the surface of the sample oxidized naturally in air for 5 h, and the density of amorphous regions is similar to that of the sample oxidized naturally in air for 5 h, but the area of ​​a single amorphous region in the sample oxidized naturally in air for 10 h is larger than that in the sample oxidized naturally in air for 5 h. The surface of the sample oxidized naturally in air for 5 d exhibits shallow-contrast amorphous regions, similar to the surface of the sample oxidized naturally in air for 5 h, but the area and density are significantly larger than those of the sample oxidized naturally in air for 5 h, and there is a trend of dediscretization where the amorphous regions are interconnected. The above results indicate that the area and density of amorphous regions can be controlled by changing the oxidation method and oxidation time. Meanwhile, the results of natural oxidation of samples in air for 5 days show that the upper limit of oxidation time for oxidation-induced discrete amorphous regions is about 5 days. If the oxidation time exceeds this time window too much, it may lead to overall amorphization of the sample.

[0073] (2) X-ray photoelectron spectroscopy

[0074] X-ray photoelectron spectroscopy was performed on two-dimensional iron-germanium-tellurium nanosheet powder that was not oxidized in a controlled manner (Example 1) and powder that was naturally oxidized in air for 5 days (Example 4). Figure 7 (a) and Figure 7 (c) in the figure shows the full spectrum of the two samples, respectively. Compared with the uncontrolled oxidation sample, the O1s signal of the 5d sample is significantly enhanced, indicating that the oxygen-related components on the sample surface increase after oxygen treatment.

[0075] Figure 7 (b) and Figure 7 The (d) spectra in the figure represent the fine Fe 2p spectra of the uncontrolled oxidation sample and the naturally oxidized sample after 5 days, respectively. Fe appears in the naturally oxidized sample after 5 days. 3+ The characteristics of the relevant oxidation peaks indicate that oxygen treatment is accompanied by changes in the chemical valence state of iron. Combined with the enhancement of the O1s signal, this eliminates the possibility of attributing the structural changes solely to surface physisorption based on morphological observation, and supports the view that controlled oxidation leads to changes in both surface chemistry and local structure.

[0076] (3) Changes in coercivity

[0077] Hysteresis loop measurements were performed at 2 K on a two-dimensional iron-germanium-tellurium nanosheet sample that had not undergone controlled oxidation (Example 1). Figure 8 As shown, the coercivity obtained from the zero-crossing position of magnetization is approximately 3300 Oe.

[0078] Two-dimensional iron-germanium-tellurium nanosheet powder was naturally oxidized in air for 5 days (Example 4), and hysteresis loop measurements were performed at 2K. Figure 9 As shown, the coercivity of the sample is approximately 4300 Oe. Relative to... Figure 8 The result shows that the coercivity increases by approximately 1000 Oe, or about 30%, to approximately 3300 Oe. These results indicate that within the processing window of this invention, air oxidation not only causes overall magnetic degradation but can also be accompanied by an increase in coercivity.

[0079] Figures 4 to 6 The structural characterization corresponds to the 5-hour natural oxidation time point. Figure 7 and Figure 9 Surface chemical and magnetic characterizations are presented at 5-day spontaneous oxidation time points. Different time points are used to illustrate the evolutionary evidence from local structural changes to surface valence state changes and increased coercivity within the same spontaneous oxidation process window, and are not presented as all tests performed simultaneously on the same physical sample. Preferably, in subsequent process calibration, samples from the same preparation batch are randomly divided, and the time points are compared under the same measurement procedure.

[0080] Mechanism of action explanation

[0081] Unbound by any specific theory, the applicant believes that the discrete amorphous regions generated on the surface of a crystalline iron-germanium-tellurium matrix by controlled oxidation form localized structures and magnetic energy differences. When an external magnetic field drives the domain walls to move, this localized difference increases the energy required for the domain walls to cross the corresponding positions, thus requiring a higher external field to complete the magnetization reversal, which macroscopically manifests as an increase in coercivity. Figure 13 This illustrates the possible mechanism. Figure 13 This is only intended to explain one possible mechanism and is not intended to limit the invention to being implemented through this mechanism.

[0082] The size, area fraction, and spatial density of amorphous regions can be affected by oxidation time, oxidation temperature, oxygen content in the atmosphere, powder spreading thickness, nanosheet surface cleanliness, and nanosheet thickness distribution. Therefore, a processing window for a specific batch of material can be established by calibrating these parameters. The processing window preferably satisfies the following conditions: preservation of the main crystalline structure; appearance of discrete amorphous regions on the surface; higher coercivity after treatment than the reference sample; and no unacceptable reduction in the target magnetic properties due to excessive oxidation. The cathode and anode are not limited to flat platinum sheets; platinum rods, platinum wires, or other conductive electrodes that are stable under the appropriate electrolyte and potential window and can achieve cation intercalation can be used. For different electrode areas, the potential, current, and processing time should be adjusted accordingly to allow the bulk crystals to expand sufficiently and avoid overall decomposition.

[0083] Furthermore, while maintaining the cathodic cation intercalation mechanism, the alkyl length or anion type of the quaternary ammonium salt can be changed, and residual intercalating agent can be removed through a washing step. The washing, centrifugation, and filtration parameters can be adjusted according to the lateral size, thickness, and dispersion stability of the nanosheets.

[0084] The oxygen-containing atmosphere is not limited to laboratory air; it can also be a mixture of oxygen and inert gas with controlled oxygen content. When using a mixture, the oxidation dosage should be controlled by a combination of oxygen partial pressure, temperature, and time to ensure that the treated material retains the composite structure of a crystalline iron-germanium-tellurium matrix and discrete amorphous regions.

[0085] The powder obtained by this invention can be further dispersed, pressed, coated, or compounded for use as a raw material for magnetic storage, spintronics, or magnetic sensing functional materials. Specific device structures and operating temperatures can be designed separately according to application requirements without affecting the protection of the material processing method and the resulting microstructured products by this invention.

[0086] The above are merely preferred embodiments of the present invention. Any equivalent substitutions made by those skilled in the art for electrode shape, container, dispersion method, solid-liquid separation method, oxidizing atmosphere, and processing procedure without departing from the technical concept defined in the claims should fall within the protection scope of the present invention.

Claims

1. A method for enhancing the coercivity of two-dimensional iron-germanium-tellurium nanosheets by oxidation-induced amorphous pinning regions, characterized in that, Includes the following steps: S1, using bulk iron-germanium-tellurium material as a cathode for electrochemical cation intercalation, thereby increasing the interlayer spacing of the bulk iron-germanium-tellurium material; S2, the intercalated iron-germanium-tellurium material is placed in an organic solvent and mechanically disturbed to obtain a dispersion containing two-dimensional iron-germanium-tellurium nanosheets; S3, the dispersion is centrifuged and washed multiple times, the upper suspension containing two-dimensional nanosheets is collected, and then filtered and vacuum dried in sequence to obtain two-dimensional iron-germanium-tellurium nanosheets. S4, the two-dimensional iron-germanium-tellurium nanosheets are placed in an oxygen-containing atmosphere for controlled oxidation treatment, so that while retaining the crystalline iron-germanium-tellurium matrix, the two-dimensional iron-germanium-tellurium nanosheets form spatially separated oxidation-induced amorphous regions on the surface of the crystalline iron-germanium-tellurium matrix.

2. The method as described in claim 1, characterized in that, The stoichiometric formula for bulk iron-germanium-tellurium material is Fe. 3-x GeTe2, where 0≤x≤0.15, has a hexagonal crystal system with space group P63 / mmc.

3. The method as described in claim 1, characterized in that, The electrochemical cation intercalation uses a dual-electrode system, in which a bulk iron-germanium-tellurium material is fixed on a platinum sheet, platinum wire or platinum rod as a cathode, and another platinum electrode is used as an anode. The cathode and anode are immersed in an electrolyte containing quaternary ammonium salt and aprotic organic solvent, and the cathode is at a negative potential relative to the anode.

4. The method as described in claim 3, characterized in that, The aprotic organic solvent is propylene carbonate or N,N-dimethylformamide; and / or, the quaternary ammonium salt is selected from any one of tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium bromide, and tetraheptylammonium bromide.

5. The method as described in claim 3, characterized in that, The concentration of quaternary ammonium salt in the electrolyte is 0.5M; and / or, the distance between the cathode and anode is 1~1.5cm; and / or, the potential difference between the cathode and anode is 15~35V, and the cathode potential is set to a negative DC potential; and / or, the electrolysis time is 20min.

6. The method as described in claim 1, characterized in that, The intercalated iron-germanium-tellurium material is placed in an organic solvent, propylene carbonate or N,N-dimethylformamide, and mechanical disturbance is applied by ultrasound, oscillation or a combination thereof to exfoliate the nanosheets from the bulk material and form a suspension.

7. The method as described in claim 1, characterized in that, The dispersion was centrifuged and washed multiple times. The specific process was as follows: the dispersion was centrifuged at high speed, the supernatant was removed, the washing medium was added and the precipitate was redispersed, and this process was repeated multiple times to remove residual electrolytes, intercalating agents and by-products. Then, the dispersion was centrifuged at low speed to remove the thick blocks that were not fully peeled off and the upper suspension containing two-dimensional nanosheets was collected. The cleaning medium is propylene carbonate, N,N-dimethylformamide, or anhydrous ethanol.

8. The method as described in claim 1, characterized in that, The upper suspension containing two-dimensional nanosheets was filtered and vacuum dried to obtain two-dimensional iron-germanium-tellurium nanosheets.

9. The method as described in claim 1, characterized in that, The controlled oxidation treatment adopts a natural oxidation method: placing it in air for 5 hours to 5 days; or a heated oxidation method: treating it in air at 80 to 150°C for 15 to 60 minutes; after treatment, the crystalline iron-germanium-tellurium matrix is ​​retained, and spatially separated oxidation-induced amorphous regions are formed on the matrix surface.

10. A two-dimensional iron-germanium-tellurium magnetic material, characterized in that, Prepared by the method described in any one of claims 1-9.